An iron-based rare earth hard alloy and its preparation method and application, an iron-based rare earth hard alloy reinforced shovel tooth and its preparation method
Through the brazing of iron-based rare earth carbide and shovel teeth, the alloying of WC powder and iron-based powder and the optimization of rare earth oxides, the problems of short service life and low cost-effectiveness are solved, and high hardness and high quality are achieved Wear resistance and low cost spade tooth reinforcement.
Patent Information
- Application Number
- CN202310213569.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The existing shovel teeth strengthening methods face problems such as high cost of high-performance matrix materials and reinforcement materials and difficult bonding methods of strengthening materials and substrates, resulting in short service life and low cost-effectiveness.
Iron-based rare earth carbide is combined with shovel teeth through simple brazing, WC powder is used as hard phase and iron-based powder is used as bonding phase, and nickel alloyed and cobalt solid solution strengthening, and rare earth oxide La2O3 is added to optimize bonding. The junction phase components form a multi-order solid solution, which improves hardness and wear resistance.
It achieves high hardness and high wear resistance of shovel teeth, improves service life, reduces the cost of strengthening shovel teeth, solves the problems of fast wear and low cost performance caused by low hardness, and is simple and convenient for large-scale production.
Smart Images

Figure CN116083776B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shovel teeth, and in particular to an iron-based rare earth hard alloy and a preparation method and application thereof, an iron-based rare earth hard alloy reinforced shovel tooth and a preparation method thereof. Background Art
[0002] With the increasing development of social economy, the construction machinery industry is also making continuous progress. As a kind of commonly used construction machinery, the excavator has important shovel teeth when working. The service life of the shovel teeth directly affects its work efficiency and economic benefits. Optimizing the performance of the shovel teeth and thus improving the service life of the shovel teeth is the basis of the current construction machinery industry. Fracture, corrosion and wear are the three major failure forms of shovel teeth, among which the most common and main failure form is wear. When in service, the shovel teeth are subjected to strong composite impact loads such as extrusion, shearing, bending and severe wear. Generally, the service life of the shovel teeth is only 3 to 4 weeks. This seriously restricts the development of the mechanical engineering industry and brings huge economic losses. At present, the high-end shovel tooth market has long been occupied by foreign countries, with high prices and low cost performance. Therefore, breaking through and solving the technical bottleneck of low service life of shovel teeth and developing low-cost, high-performance and high-wear-resistant shovel teeth are the hot spots and development trends of research and development at this stage.
[0003] At present, the main methods for strengthening the shovel teeth are the development of base materials and strengthening materials (shovel teeth coated with wear-resistant materials). Chinese patent application No. 202010423344.9 discloses a method for preparing ceramic-reinforced wear-resistant shovel teeth, including: placing alloy steel raw materials into a medium-frequency induction furnace to melt and obtain molten steel, casting to obtain a shovel tooth matrix, grinding and cleaning the worn parts, and then coating them with ceramic slurry, heating and curing; the raw materials of the ceramic slurry include by weight: 38-42 parts of aluminum oxide, 10-18 parts of silicon carbide, 7-9 parts of zirconium oxide, 1-5 parts of chromium oxide, 0.1-0.35 parts of nanocarbon materials, 2-4 parts of high-alumina cement, 1-3 parts of tungsten carbide, 0.5-2 parts of cerium oxide and 35-55 parts of aluminum dihydrogen phosphate; the nanocarbon material is a mixture of carbon nanotubes and graphene in a weight ratio of 1-4:2-5. Although this method increases the wear resistance of the shovel teeth by wear-resistant ceramics, the ceramic slurry strengthening layer has a poor match with the shovel tooth alloy matrix, poor bonding, and is easy to fall off. Chinese patent CN112111683A (application number CN202011008891.7) discloses an iron-nickel-cobalt type tungsten carbide wear-resistant material, wherein the hard phase comprises coarse-grained tungsten carbide and fine-grained tungsten carbide, the coarse grain size is ≥20μm, the fine grain size is ≤3μm, and the bonding phase powder comprises the following components in parts by weight: iron powder: 55-75 parts, nickel powder: 15-25 parts, and cobalt powder: 10-20 parts. The preparation method comprises: high-energy ball milling the fine-grained tungsten carbide with iron powder, nickel powder and cobalt powder to obtain a primary slurry; adding coarse-grained tungsten carbide and high-energy ball milling to obtain a secondary slurry; adding the rubber solution after drying and screening to mix; drying and screening again to obtain a mixture; sintering after pressing and molding, and cooling with the furnace to obtain the iron-nickel-cobalt type tungsten carbide wear-resistant material. Although this method prepares iron-nickel-cobalt type hard alloy, high-energy ball milling reduces the grain size of tungsten carbide and reduces the overall wear resistance of the alloy.
[0004] Therefore, the existing shovel tooth strengthening method faces the problems of high cost of high-performance matrix materials and reinforcement materials, and difficult combination of reinforcement materials and matrix. Summary of the invention
[0005] The purpose of the present invention is to provide an iron-based rare earth cemented carbide and its preparation method and application, an iron-based rare earth cemented carbide reinforced shovel tooth and its preparation method, the iron-based rare earth cemented carbide can be combined with the shovel tooth by simple brazing and produce a good protective effect, thereby realizing low-cost and high-performance strengthening of the shovel tooth.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an iron-based rare earth hard alloy, comprising the following steps:
[0008] Fe powder, Ni powder, Co powder and La2O3 are mixed, the obtained iron-based rare earth binder mixture is subjected to a first stage of ball milling, WC powder and a forming agent are directly added to the obtained mixed slurry, a second stage of ball milling is carried out, and vacuum drying is carried out to obtain an iron-based rare earth cemented carbide mixture;
[0009] The iron-based rare earth hard alloy mixture is pressed, sintered and passivated in sequence to obtain the iron-based rare earth hard alloy.
[0010] Preferably, in the iron-based rare earth binder mixture, the mass percentages of Fe powder, Ni powder, Co powder and La2O3 are: Fe 45-60%; Ni 23-35%; Co 15-25%; La2O3 2-7%.
[0011] Preferably, taking the total mass percentage of the iron-based rare earth binder mixture and the WC powder as 100%, the mass percentage of the WC powder is 70-85%, and the mass percentage of the iron-based rare earth binder mixture is 15-30%.
[0012] Preferably, the solid-liquid ratio of the first stage of ball milling mixing is 1kg:150-280mL, the ball-to-material mass ratio is (3-5):1, and the ball milling time is 3-10h; the solid-liquid ratio of the second stage of ball milling mixing is 1kg:150-280mL, the ball-to-material mass ratio is (1-3):1, and the ball milling time is 4-8h.
[0013] Preferably, the pressing strength of the pressing molding is 70-140 MPa; the sintering temperature is 1420-1560° C., and the holding time is 60-90 min; and the passivation time is 1.5-4 h.
[0014] The present invention provides an iron-based rare earth hard alloy prepared by the preparation method described in the above technical solution.
[0015] The present invention provides the application of the iron-based rare earth hard alloy described in the above technical solution in the shovel teeth.
[0016] The present invention provides a method for preparing an iron-based rare earth hard alloy reinforced shovel tooth, comprising the following steps:
[0017] After the brazing filler metal is coated on the lower end of the iron-based rare earth hard alloy, it is embedded in the shovel teeth and brazed under vacuum heating conditions to obtain the iron-based rare earth hard alloy reinforced shovel teeth;
[0018] The iron-based rare earth hard alloy is the iron-based rare earth hard alloy described in the above technical solution;
[0019] The iron-based rare earth hard alloy is a long T-shaped structure, with an arc-shaped top and a trapezoidal bottom.
[0020] Preferably, the solder is an aluminum-based solder, a silver-based solder or a copper-based solder; the vacuum degree of the vacuum heating is 1×10 -2 ~1×10 -3 Pa, heating temperature is 400~1200℃.
[0021] The present invention provides an iron-based rare earth hard alloy reinforced shovel tooth prepared by the preparation method described in the above technical solution.
[0022] The invention provides a preparation method of an iron-based rare earth cemented carbide. The invention adopts WC powder as a hard phase, which has good wear resistance, and uses iron-based powder as a bonding phase. The wettability and strength of the bonding phase are improved through the solid solution strengthening effect of alloying nickel and cobalt, thereby forming a multi-element ordered solid solution. At the same time, rare earth oxide La2O3 is added to the iron-based bonding phase to optimize the bonding phase composition, and the toughening and grain boundary purification effects of the rare earth La2O3 are brought into play, so as to obtain a coarse-grained iron-based rare earth cemented carbide with high hardness and good wear resistance.
[0023] The iron-based rare earth cemented carbide of the present invention can effectively protect the shovel tooth matrix, greatly improve the hardness, wear resistance and service life of the shovel tooth, and strengthen the compound of the iron-based rare earth cemented carbide and ordinary shovel teeth through a simple brazing method to obtain a high-strength bonding force, and combine the wear resistance of the cemented carbide with the shovel tooth, which not only retains the toughness of the shovel tooth matrix, but also has high hardness and high wear resistance. The high hardness and high wear resistance of ordinary shovel teeth are strengthened, and the overall process is simple and easy to operate, which is conducive to the large-scale batch production of high-wear-resistant iron-based rare earth cemented carbide strengthened shovel teeth; the present invention adopts iron-based rare earth cemented carbide to strengthen the shovel teeth, which can reduce the cost of strengthening the shovel teeth, thereby obtaining the maximum cost-effectiveness, and solves the problems of fast wear, frequent replacement and low cost-effectiveness caused by the low hardness of the shovel teeth of key engineering components during actual use.
[0024] The present invention realizes uniform mixing of iron powder, nickel powder, cobalt powder and rare earth La2O3 in a binder phase through the first stage of ball milling mixing, and realizes rapid and uniform mixing of WC powder and a binder phase mixture through the second stage of ball milling mixing, thereby greatly reducing the breakage of WC powder caused by ball milling, thereby preparing high-performance coarse-grained iron-based rare earth cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a flow chart of the method for preparing the iron-based rare earth hard alloy and the reinforced shovel teeth thereof of the present invention;
[0026] Figure 2 This is a schematic diagram of the grooving process of the toothing (side view);
[0027] Figure 3 This is a schematic diagram of a finished product of an iron-based rare earth cemented carbide;
[0028] Figure 4This is a schematic diagram of the finished scraper tooth after brazing and strengthening of iron-based rare earth cemented carbide;
[0029] Figure 5 Metallographic structure photos of the iron-based rare earth cemented carbide prepared in Example 1: (a) 200×; (b) 1000×;
[0030] Figure 6 Metallographic structure photos of the iron-based rare earth cemented carbide prepared in Example 3: (a) 200×; (b) 1000×. DETAILED DESCRIPTION
[0031] like Figure 1 As shown, the present invention provides a method for preparing an iron-based rare earth hard alloy, comprising the following steps:
[0032] Fe powder, Ni powder, Co powder and La2O3 are mixed, the obtained iron-based rare earth binder mixture is subjected to a first stage of ball milling, WC powder and a forming agent are directly added to the obtained mixed slurry, a second stage of ball milling is carried out, and vacuum drying is carried out to obtain an iron-based rare earth cemented carbide mixture;
[0033] The iron-based rare earth hard alloy mixture is pressed, sintered and passivated in sequence to obtain the iron-based rare earth hard alloy.
[0034] In the present invention, unless otherwise specified, the required raw materials or instruments are commercially available products well known to those skilled in the art.
[0035] The invention mixes Fe powder, Ni powder, Co powder and La2O3, and performs a first stage ball milling mixing on the obtained iron-based rare earth binder mixture to obtain a mixed slurry.
[0036] In the present invention, the purity of the Fe powder, Ni powder and Co powder is preferably independently ≥99.5%, the particle size is preferably independently 2-5 μm, and the particle size of the La2O3 is preferably ≤1 μm.
[0037] In the present invention, the mass percentages of Fe powder, Ni powder, Co powder and La2O3 in the iron-based rare earth binder mixture are preferably: Fe 45-60%; Ni 23-35%; Co 15-25%; La2O3 2-7%.
[0038] In the present invention, the mass percentages of Fe powder, Ni powder, Co powder and La2O3 are more preferably: Fe 50-55%, further preferably 50%; Ni 25-35%, further preferably 30%; Co 17-20%; La2O3 3-5%.
[0039] In the present invention, the first stage of ball milling mixing is preferably carried out in a ball mill barrel, the ball milling medium used is preferably anhydrous ethanol, and the grinding balls used are preferably cemented carbide balls.
[0040] In the present invention, the solid-liquid ratio of the first stage ball milling mixing is preferably 1kg:150-280mL, more preferably 1kg:180-260mL, further preferably 1kg:200-240mL, the ball-to-material mass ratio is preferably (3-5):1, more preferably 4:1, and the ball milling time is preferably 3-10h, more preferably 8h.
[0041] After obtaining the mixed slurry, the present invention directly adds WC powder and a molding agent into the obtained mixed slurry, performs a second stage of ball milling and mixing, and then vacuum dries to obtain an iron-based rare earth hard alloy mixture.
[0042] In the present invention, the purity of the WC powder is preferably ≥99.9%, and the particle size is preferably ≥25 μm, more preferably 25-40 μm, that is, ultra-coarse-grained WC powder.
[0043] In the present invention, taking the total mass percentage of the iron-based rare earth binder mixture and WC powder as 100%, the mass percentage of the WC powder is preferably 70-85%, more preferably 75-80%, and the mass percentage of the iron-based rare earth binder mixture is preferably 15-30%, more preferably 20-25%.
[0044] In the present invention, the molding agent preferably includes paraffin wax; the mass of the molding agent is preferably 1.5-3.0% of the total mass of the iron-based rare earth binder mixture and WC powder, and more preferably 2.0-2.5%.
[0045] In the present invention, the ball milling medium used in the second stage of ball milling is preferably anhydrous ethanol, and the grinding balls used are preferably cemented carbide balls.
[0046] In the present invention, the solid-liquid ratio of the second stage ball milling mixing is preferably 1kg:150-280mL, more preferably 1kg:210-260mL, the ball-to-material mass ratio is preferably (1-3):1, more preferably 2:1, and the ball milling time is preferably 4-8h, more preferably 5-7h, and further preferably 6h.
[0047] After the second stage of ball milling, the present invention preferably vacuum-dries the obtained material and passes it through a 60-mesh screen to obtain an iron-based rare earth hard alloy mixture. The present invention has no special limitation on the vacuum drying, and it can be carried out according to a process well known in the art.
[0048] After obtaining the iron-based rare earth hard alloy mixture, the present invention sequentially performs compression molding, sintering and passivation on the iron-based rare earth hard alloy mixture to obtain the iron-based rare earth hard alloy.
[0049] The present invention preferably loads the iron-based rare earth cemented carbide mixture into a mold and performs compression molding by cold isostatic pressing. In the present invention, the compression strength of the compression molding is preferably 70 to 140 MPa, more preferably 90 to 110 MPa, and further preferably 100 MPa. The present invention has no special limitation on the time of the compression molding, which can be adjusted according to actual needs.
[0050] After the compression molding is completed, the present invention preferably performs an apparent quality inspection on the obtained compact after molding. The present invention has no special limitation on the method of the apparent quality inspection, and it can be performed according to methods well known in the art.
[0051] The present invention preferably loads the obtained formed green sheet into a degreasing and sintering integrated furnace for sintering; the sintering atmosphere is preferably argon, and the sintering pressure is preferably 3-7 MPa, more preferably 5-6 MPa; the sintering temperature is preferably 1420-1560°C, more preferably 1450-1520°C, further preferably 1480-1500°C, and the holding time is preferably 60-90 min; and the furnace is cooled after sintering.
[0052] The present invention preferably performs surface cleaning and polishing of the sintered cemented carbide in a sandblaster, and then performs passivation in a ball mill to obtain an iron-based rare earth cemented carbide; the passivation time is preferably 1.5 to 4 hours, more preferably 3 hours. The present invention has no special limitation on the specific process of the passivation, and it can be performed according to the process well known in the art.
[0053] The present invention provides an iron-based rare earth hard alloy prepared by the preparation method described in the above technical solution.
[0054] The present invention provides the application of the iron-based rare earth hard alloy described in the above technical solution in the shovel teeth.
[0055] like Figure 1 As shown, the present invention provides a method for preparing an iron-based rare earth cemented carbide reinforced shovel tooth, comprising the following steps:
[0056] After the brazing filler metal is coated on the lower end of the iron-based rare earth hard alloy, it is embedded in the shovel teeth and brazed under vacuum heating conditions to obtain the iron-based rare earth hard alloy reinforced shovel teeth;
[0057] The iron-based rare earth hard alloy is the iron-based rare earth hard alloy described in the above technical solution;
[0058] The iron-based rare earth hard alloy is in a long T-shaped structure, with an arc-shaped top and a trapezoidal bottom.
[0059] In the present invention, the solder is preferably an aluminum-based solder, a silver-based solder or a copper-based solder. The present invention has no special limitation on the solder and its source, and any commercially available product known in the art may be used.
[0060] The present invention has no special limitation on the shovel teeth, and any commercially available product known in the art can be used; more preferably, the universal 460 type shovel teeth are used.
[0061] In the present invention, before embedding the shovel teeth, the shovel teeth are preferably processed, and the processing method is preferably integral casting with grooves or linear cutting of the shovel teeth. The groove shape of the shovel teeth is preferably a trapezoidal shape that is entirely transversely transparent, and the dimensions are preferably: upper bottom 50-80mm, more preferably 60-70mm; lower bottom 30-50mm, more preferably 35mm; height 25-35mm, more preferably 30-33mm, thickness 3-8mm, more preferably 5-7mm, such as Figure 2 shown.
[0062] The present invention preferably embeds the iron-based rare earth hard alloy coated with solder into the trapezoidal groove of the tooth after slotting.
[0063] In the present invention, when the iron-based rare earth hard alloy is used to strengthen the shovel teeth, the shape and size of the iron-based rare earth hard alloy are as follows: Figure 3 As shown, the iron-based rare earth cemented carbide is a long T-shaped structure, the top end is arc-shaped, the bottom end is trapezoidal, and the connection between the top end and the bottom end is also arc-shaped. In the present invention, the size of the long T-shaped structure is preferably adjusted according to the size of the shovel teeth and the grooves in the shovel teeth according to actual conditions. In a specific embodiment of the present invention, the radius of the top arc ( Figure 3 The radius of the arc at the connection between the top and the bottom ( Figure 3 R2) is preferably 1-3 mm, more preferably 1.5-2.0 mm; the distance between the highest point and the lowest point of the top arc is 12 mm, the distance between the highest point of the top arc and the connection between the top and the lower end is 10 mm, the height of the trapezoid is 30 mm, the thickness of the trapezoid is 6 mm, the distance between the lowest points on both sides of the top arc is 12 mm, and the other dimensions are as follows: Figure 3 .
[0064] The present invention coats the lower end of the iron-based rare earth cemented carbide with brazing filler metal and then embeds it into the shovel tooth. On the one hand, the tip of the shovel tooth can be fully protected. On the other hand, the tip size of the shovel tooth is maintained, which is beneficial to the long-term stable operation of the shovel tooth.
[0065] The present invention preferably attaches the brazing material to the joint portion between the iron-based rare earth hard alloy and the shovel tooth, and knocks it into the shovel tooth. The present invention has no special limitation on the amount of the brazing material, which can be adjusted according to actual needs.
[0066] In the present invention, the vacuum heating is preferably carried out in a vacuum furnace; the vacuum degree of the vacuum heating is preferably 1×10 -2 ~1×10 -3 Pa, more preferably (3 to 8)×10 -3 Pa is more preferably (4 to 5)×10 -3 Pa, the heating temperature is preferably 400 to 1200°C, more preferably 600 to 1150°C, and further preferably 900 to 1100°C.
[0067] After completing the brazing, the present invention preferably cools the brazed shovel teeth and then cleans and polishes the surface in a sandblasting machine to obtain iron-based rare earth cemented carbide reinforced shovel teeth (iron-based rare earth cemented carbide and shovel teeth form a metallurgical bond); the present invention has no special limitation on the cleaning and polishing, and it can be carried out according to the process well known in the art.
[0068] The present invention provides an iron-based rare earth hard alloy reinforced shovel tooth prepared by the preparation method described in the above technical solution. The schematic diagram of the structure of the iron-based rare earth hard alloy reinforced shovel tooth prepared by the present invention is as follows Figure 4 shown.
[0069] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0070] In the following examples, the purity of WC powder is 99.9% and the particle size is 25-40 μm;
[0071] The purity of Fe, Ni and Co powders is 99.5%, and the particle size is 2-5 μm; the particle size of La2O3 powder is 0.8-1.0 μm; Example 1
[0072] a. Prepare an iron-based rare earth binder mixture: mix Fe, Ni, Co powders and rare earth La2O3 according to the following mass percentages: Fe: 45wt.%; Ni: 35wt.%; Co: 15wt.%; rare earth La2O3: 5wt.%, wherein the particle sizes of Fe, Ni, and Co are 5μm, 2μm, and 3μm respectively, and the particle size of La2O3 powder is 0.8μm;
[0073] b. Continuous segmented ball milling 1: Add the iron-based rare earth binder mixture into the ball mill barrel and grind with carbide balls at a ball-to-material ratio of 4:1. The ball milling medium is anhydrous ethanol, the solid-liquid ratio is 240 mL / kg material, and the ball milling time is 6 h.
[0074] c. Continuous segmented ball milling and mixing 2: directly add ultra-coarse-grained WC powder with a particle size of 35 μm to the ball-milled iron-based rare earth cemented carbide binder mixture slurry, and mix them according to the following mass percentages: 85wt.% of ultra-coarse-grained WC powder and 15wt.% of iron-based rare earth binder mixture, and add 2.5% of paraffin wax as a molding agent accounting for the total mass of the raw materials (WC powder and iron-based rare earth binder mixture); add anhydrous ethanol and cemented carbide balls, with anhydrous ethanol solid-liquid ratio of 240mL / kg material and a ball-to-material ratio of 2:1, and ball mill again for 6h; after vacuum drying, sieve through a 60-mesh screen to granulate into an iron-based rare earth cemented carbide mixture.
[0075] d. Pressing and molding: the iron-based rare earth cemented carbide mixture is loaded into a mold, and the mixture is pressed and molded by cold isostatic pressing. The cold isostatic pressing strength is 100MPa, and the apparent quality inspection of the powder compact after molding is performed;
[0076] e. Sintering: The powder compacts that have passed the inspection are loaded into a degreasing-sintering integrated furnace, and low-pressure sintering is carried out at 1520°C for 60 minutes under an argon protective atmosphere. The sintering pressure is 5MPa. After sintering, the powder compacts are cooled with the furnace to obtain iron-based rare earth cemented carbide.
[0077] f. Sandblasting passivation: The sintered cemented carbide is surface cleaned and polished in a sandblasting machine, and then passivated in a ball mill for 3 hours to obtain an iron-based rare earth cemented carbide.
[0078] g. Tooth-cutting processing: Ordinary tooth-cutting wire cutting grooves are used, and the groove dimensions are upper bottom 50mm, lower bottom 30mm, height 30mm, and thickness 5mm.
[0079] h. Brazing: The iron-based rare earth hard alloy is coated with aluminum-based brazing filler metal and embedded into the processed scraper teeth. The scraper teeth are vacuum heated to 1100°C and the vacuum degree is 5×10 -3 Pa.
[0080] i. Sandblasting: After the brazed shovel teeth are cooled, the surface is cleaned and polished in a sandblasting machine to obtain iron-based rare earth carbide reinforced shovel teeth.
[0081] Example 2
[0082] a. Prepare an iron-based rare earth binder mixture: mix Fe, Ni, Co powders and rare earth La2O3 according to the following mass percentages: Fe: 55wt.%; Ni: 25wt.%; Co: 17wt.%; rare earth La2O3: 3wt.%, wherein the particle sizes of Fe, Ni, and Co are 2μm, 3μm, and 3μm respectively, and the particle size of La2O3 powder is 1.0μm;
[0083] b. Continuous segmented ball milling 1: Add the iron-based rare earth binder mixture into the ball mill barrel and grind with carbide balls at a ball-to-material ratio of 5:1. The ball milling medium is anhydrous ethanol, the solid-liquid ratio is 210 mL / kg material, and the ball milling time is 8 h.
[0084] c. Continuous segmented ball milling and mixing 2: directly add ultra-coarse-grained WC powder with a particle size of 40 μm to the ball-milled iron-based rare earth cemented carbide binder mixture slurry; mix them according to the following mass percentages: 80wt.% of ultra-coarse-grained WC powder and 20wt.% of iron-based rare earth binder mixture, and add 2.0% of paraffin wax as a molding agent accounting for the total mass of the raw materials (WC powder and iron-based rare earth binder mixture); add anhydrous ethanol and cemented carbide balls, with a solid-liquid ratio of 210mL / kg material and a ball-to-material ratio of 1:1, and ball mill again for 5 hours. After vacuum drying, sieve through a 60-mesh screen to granulate into an iron-based rare earth cemented carbide mixture.
[0085] d. Pressing and molding: The iron-based rare earth cemented carbide mixture is loaded into a mold and pressed into a mold by cold isostatic pressing. The cold isostatic pressing strength is 90 MPa, and the powder compact after molding is inspected for apparent quality;
[0086] e. Sintering: The qualified powder compact is loaded into a degreasing-sintering integrated furnace, and low-pressure sintering is carried out at 1500°C for 90 minutes under an argon protective atmosphere. The sintering pressure is 6MPa. After sintering, the powder compact is cooled with the furnace to obtain an iron-based rare earth cemented carbide.
[0087] f. Sandblasting passivation: The sintered iron-based rare earth cemented carbide is surface cleaned and polished in a sandblasting machine, and then passivated in a ball mill for 1.5 hours to obtain an iron-based rare earth cemented carbide.
[0088] g. Tooth removal processing: Ordinary tooth removal wire cutting groove, the groove size is 60mm upper bottom, 35mm lower bottom, 33mm height, 7mm thickness.
[0089] h. Brazing: The iron-based rare earth hard alloy is coated with aluminum-based brazing filler metal and embedded into the processed scraper teeth. The scraper teeth are vacuum heated to 600°C and the vacuum degree is 4×10 -3 Pa.
[0090] i. Sandblasting and polishing: After the brazed shovel teeth are cooled, the surface is cleaned and polished in a sandblasting machine to obtain highly wear-resistant iron-based rare earth carbide reinforced shovel teeth with a friction coefficient of 0.49 in the top area of the shovel teeth.
[0091] Example 3
[0092] a. Prepare an iron-based rare earth binder mixture: mix Fe, Ni, Co powders and rare earth La2O3 according to the following mass percentages: Fe: 60wt.%; Ni: 25wt.%; Co: 20wt.%; rare earth La2O3: 5wt.%, wherein the particle sizes of Fe, Ni, and Co are 3μm, 5μm, and 2μm respectively, and the particle size of La2O3 powder is 0.8μm;
[0093] b. Continuous segmented ball milling 1: Add the iron-based rare earth binder mixture into the ball mill barrel and grind with carbide balls at a ball-to-material ratio of 3:1. The ball milling medium is anhydrous ethanol, the solid-liquid ratio is 180 mL / kg material, and the ball milling time is 3 h.
[0094] c. Continuous segmented ball milling and mixing 2: directly add ultra-coarse-grained WC powder with a particle size of 30 μm to the ball-milled iron-based rare earth cemented carbide binder mixture slurry; mix them according to the following mass percentages: 75wt.% of ultra-coarse-grained WC powder and 25wt.% of iron-based rare earth binder mixture, and add 1.5% of paraffin wax as a molding agent accounting for the total mass of the raw materials (WC powder and iron-based rare earth binder mixture); add anhydrous ethanol and cemented carbide balls, specifically, anhydrous ethanol solid-liquid ratio of 260mL / kg material, ball-to-material ratio of 2:1, and ball mill again for 7h. After vacuum drying, sieve through a 60-mesh screen to granulate into an iron-based rare earth cemented carbide mixture.
[0095] d. Compression molding: the mixture is loaded into a mold and pressed into shape by cold isostatic pressing. The cold isostatic pressing strength is 110 MPa, and the powder compact after molding is inspected for apparent quality.
[0096] e. Sintering: The qualified powder compact is loaded into a degreasing-sintering integrated furnace, and low-pressure sintering is performed at 1480°C for 60 minutes under an argon protective atmosphere. The sintering pressure is 5 MPa. After sintering, the powder compact is cooled with the furnace to obtain an iron-based rare earth cemented carbide.
[0097] f. Sandblasting passivation: The sintered iron-based rare earth cemented carbide is surface cleaned and polished in a sandblasting machine, and then passivated in a ball mill for 2 hours to obtain an iron-based rare earth cemented carbide.
[0098] g. Tooth-cutting processing: Ordinary tooth-cutting wire cutting grooves are used, and the groove dimensions are upper bottom 50mm, lower bottom 30mm, height 30mm, and thickness 5mm.
[0099] h. Brazing: The iron-based rare earth cemented carbide is coated with silver-based brazing filler metal and embedded into the processed scraper teeth. The scraper teeth are vacuum heated to 900°C and the vacuum degree is 8×10 -3 Pa.
[0100] i. Sandblasting: After the brazed shovel teeth are cooled, the surface is cleaned and polished in a sandblasting machine to obtain highly wear-resistant iron-based rare earth carbide reinforced shovel teeth with a friction coefficient of 0.42 in the top area of the shovel teeth.
[0101] Example 4
[0102] a. Prepare an iron-based rare earth binder mixture: mix Fe, Ni, Co powders and rare earth La2O3 according to the following mass percentages: Fe: 46wt.%; Ni: 35wt.%; Co: 15wt.%; rare earth La2O3: 4wt.%, wherein the particle sizes of Fe, Ni, and Co are 3μm, 3μm, and 3μm respectively, and the particle size of La2O3 powder is 1.0μm;
[0103] b. Continuous segmented ball milling 1: Add the iron-based rare earth binder mixture into the ball mill barrel and grind with carbide balls at a ball-to-material ratio of 4:1. The ball milling medium is anhydrous ethanol, the solid-liquid ratio is 200 mL / kg material, and the ball milling time is 10 h.
[0104] c. Continuous segmented ball milling and mixing 2: directly add ultra-coarse-grained WC powder with a particle size of 30 μm to the ball-milled iron-based rare earth cemented carbide binder mixture slurry; mix them according to the following mass percentages: 70wt.% of ultra-coarse-grained WC powder and 30wt.% of iron-based rare earth binder mixture, and add 3.0% of paraffin wax as a molding agent accounting for the total mass of the raw materials (WC powder and iron-based rare earth binder mixture); add anhydrous ethanol and cemented carbide balls, specifically, anhydrous ethanol solid-liquid ratio of 260mL / kg material, ball-to-material ratio of 3:1, and ball mill again for 6h. After vacuum drying, sieve through a 60-mesh screen to granulate into an iron-based rare earth cemented carbide mixture.
[0105] d. Compression molding: the mixture is loaded into a mold and pressed into shape by cold isostatic pressing. The cold isostatic pressing strength is 100 MPa, and the powder compact after molding is inspected for apparent quality.
[0106] e. Sintering: The qualified powder compact is loaded into a degreasing-sintering integrated furnace, and low-pressure sintering is performed at 1450°C for 90 minutes under an argon protective atmosphere. The sintering pressure is 4 MPa. After sintering, the powder compact is cooled with the furnace to obtain an iron-based rare earth cemented carbide.
[0107] f. Sandblasting passivation: The sintered iron-based rare earth cemented carbide is surface cleaned and polished in a sandblasting machine, and then passivated in a ball mill for 3 hours to obtain an iron-based rare earth cemented carbide.
[0108] g. Tooth-cutting processing: Ordinary tooth-cutting wire cutting grooves are used, and the groove dimensions are upper bottom 70mm, lower bottom 50mm, height 35mm, and thickness 6mm.
[0109] h. Brazing: Coat the iron-based rare earth cemented carbide with copper-based brazing filler metal and embed it into the processed scraper teeth. Vacuum heat the scraper teeth to 1150℃ and the vacuum degree is 3×10 -3 Pa.
[0110] i. Sandblasting: After the brazed shovel teeth are cooled, the surface is cleaned and polished in a sandblasting machine to obtain highly wear-resistant iron-based rare earth carbide reinforced shovel teeth with a friction coefficient of 0.57 in the top area of the shovel teeth.
[0111] Example 5
[0112] b. a. Prepare an iron-based rare earth binder mixture: mix Fe, Ni, Co powders and rare earth La2O3 according to the following mass percentages: Fe: 50wt.%; Ni: 30wt.%; Co: 17wt.%; rare earth La2O3: 3wt.%, wherein the particle sizes of Fe, Ni, and Co are 4μm, 2μm, and 3μm respectively, and the particle size of La2O3 powder is 1.0μm;
[0113] b. Continuous segmented ball milling 1: Add the iron-based rare earth binder mixture into the ball mill barrel and grind with carbide balls at a ball-to-material ratio of 5:1. The ball milling medium is anhydrous ethanol, the solid-liquid ratio is 260 mL / kg material, and the ball milling time is 10 h.
[0114] c. Continuous segmented ball milling and mixing 2: directly add ultra-coarse-grained WC powder with a particle size of 40.0 μm to the ball-milled iron-based rare earth cemented carbide binder mixture slurry; mix them according to the following mass percentages: 85wt.% of ultra-coarse-grained WC powder and 15wt.% of iron-based rare earth binder mixture, and add 2.0% of paraffin wax as a molding agent accounting for the total mass of the raw materials (WC powder and iron-based rare earth binder mixture); add anhydrous ethanol and cemented carbide balls, with anhydrous ethanol solid-liquid ratio of 210mL / kg material and a ball-to-material ratio of 2:1, and ball mill again for 8h. After vacuum drying, sieve through a 60-mesh screen to granulate into an iron-based rare earth cemented carbide mixture.
[0115] d. Compression molding: the mixture is loaded into a mold and pressed into shape by cold isostatic pressing. The cold isostatic pressing strength is 100 MPa, and the powder compact after molding is inspected for apparent quality.
[0116] e. Sintering: The qualified powder compact is loaded into a degreasing-sintering integrated furnace, and low-pressure sintering is performed at 1560°C for 60 minutes under an argon protective atmosphere. The sintering pressure is 5 MPa. After sintering, the powder compact is cooled with the furnace to obtain an iron-based rare earth cemented carbide.
[0117] f. Sandblasting passivation: The sintered iron-based rare earth cemented carbide is surface cleaned and polished in a sandblasting machine, and then passivated in a ball mill for 3 hours to obtain an iron-based rare earth cemented carbide.
[0118] g. Tooth-cutting processing: Ordinary tooth-cutting wire cutting grooves are used, and the groove dimensions are upper bottom 80mm, lower bottom 50mm, height 25mm, and thickness 5mm.
[0119] h. Brazing: Coat the iron-based rare earth cemented carbide with copper-based brazing filler metal and embed it into the processed scraper teeth. Heat the scraper teeth to 1150℃ under vacuum and the vacuum degree is 7×10 -3 Pa.
[0120] i. Sandblasting: After the brazed shovel teeth are cooled, the surface is cleaned and polished in a sandblasting machine to obtain highly wear-resistant iron-based rare earth carbide reinforced shovel teeth with a friction coefficient of 0.43 in the top area of the shovel teeth.
[0121] Comparative Example 1
[0122] Use unreinforced ordinary shovel teeth, the base material is low carbon steel.
[0123] The final tooth hardness is 40HRC, and the friction coefficient of the top area of the tooth is 0.82.
[0124] Comparative Example 2
[0125] The alloy composition of the iron-based cemented carbide differs from that of Example 3 only in that the binder mixture does not contain nickel, cobalt and rare earth oxides.
[0126] The WC grain size of the final iron-based cemented carbide is 4.0 μm, the hardness is 61 HRC, the bending strength is 1820 MPa, and the friction coefficient of the top area of the shovel tooth is 0.73.
[0127] Comparative Example 3
[0128] The alloy composition of the iron-based cemented carbide differs from that of Example 3 only in that the binder mixture does not contain nickel or cobalt.
[0129] Finally, medium-grained nickel-based cemented carbide was obtained, with a WC grain size of 4.1 μm, a hardness of 61 HRC, a bending strength of 1960 MPa, and a friction coefficient of 0.71 in the top area of the shovel tooth.
[0130] Comparative Example 4
[0131] The alloy composition of the iron-based cemented carbide differs from that of Example 3 only in that the binder mixture does not contain rare earth oxides.
[0132] Finally, medium-grained nickel-based cemented carbide was obtained, with a WC grain size of 4.4 μm, a hardness of 62 HRC, a bending strength of 2110 MPa, and a friction coefficient of 0.63 in the top area of the shovel tooth.
[0133] Characterization and performance testing
[0134] 1) Figure 5 Metallographic structure photos of the iron-based rare earth cemented carbide prepared in Example 1: (a) 200×; (b) 1000×; Figure 5 It can be seen that WC has uniform grain structure and good toughness and wear resistance.
[0135] Figure 6 Metallographic structure photos of the iron-based rare earth cemented carbide prepared in Example 3: (a) 200×; (b) 1000×; Figure 6 It can be seen that the alloy structure is relatively uniform and fine, and has higher strength and wear resistance.
[0136] 2) The products of Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to performance tests: grain size GB / T6394-2002; hardness GB / T 3849.1-2015; flexural strength GB / T 3851-2015; friction coefficient GB-T12444.2-1990. The results are shown in Table 1.
[0137] Table 1 Performance data of products of Examples 1 to 5 and Comparative Examples 1 to 4
[0138]
[0139] It can be seen from Table 1 that the present invention significantly improves the performance of the shovel teeth by composite iron-based rare earth cemented carbide, which is conducive to the large-scale batch preparation of highly wear-resistant iron-based rare earth cemented carbide reinforced shovel teeth.
[0140] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an iron-based rare earth hard alloy, It is characterized in that The following steps are involved: Fe powder, Ni powder, Co powder and La 2 O 3 The obtained iron-based rare earth binder mixture is subjected to a first stage of ball milling, WC powder and a molding agent are directly added to the obtained mixed slurry, and after a second stage of ball milling, vacuum drying is performed to obtain an iron-based rare earth cemented carbide mixture; in the iron-based rare earth binder mixture, Fe powder, Ni powder, Co powder and La 2 O 3 The mass percentage is: Fe 45-60%; Ni 23-35%; Co 15-25%; La 2 O 3 2-7%; taking the total mass percentage of the iron-based rare earth binder mixture and the WC powder as 100%, the mass percentage of the WC powder is 70-85%, and the mass percentage of the iron-based rare earth binder mixture is 15-30%; The iron-based rare earth hard alloy mixture is pressed, sintered and passivated in sequence to obtain the iron-based rare earth hard alloy.
2. The preparation method according to claim 1, It is characterized in that The solid-liquid ratio of the first stage ball milling mixture is 1kg:150-280mL, the ball-to-material mass ratio is (3-5):1, and the ball milling time is 3-10h; the solid-liquid ratio of the second stage ball milling mixture is 1kg:150-280mL, the ball-to-material mass ratio is (1-3):1, and the ball milling time is 4-8h.
3. The preparation method according to claim 1, It is characterized in that The pressing strength of the pressing molding is 70-140 MPa; the sintering temperature is 1420-1560° C., and the heat preservation time is 60-90 min; and the passivation time is 1.5-4 h.
4. The iron-based rare earth hard alloy prepared by the preparation method according to any one of claims 1 to 3.
5. Application of the iron-based rare earth cemented carbide described in claim 4 in shovel teeth.
6. A method for preparing an iron-based rare earth hard alloy reinforced shovel tooth, It is characterized in that The following steps are involved: After the brazing filler metal is coated on the lower end of the iron-based rare earth hard alloy, it is embedded in the shovel teeth and brazed under vacuum heating conditions to obtain the iron-based rare earth hard alloy reinforced shovel teeth; The iron-based rare earth hard alloy is the iron-based rare earth hard alloy as claimed in claim 4; The iron-based rare earth hard alloy is a long T-shaped structure, with an arc-shaped top and a trapezoidal bottom.
7. The preparation method according to claim 6, It is characterized in that The solder is aluminum-based solder, silver-based solder or copper-based solder; the vacuum degree of the vacuum heating is 1×10 -2 ~1×10 -3 Pa, heating temperature is 400~1200℃.
8. The iron-based rare earth hard alloy reinforced shovel tooth prepared by the preparation method according to claim 6 or 7.
